A Comprehensive Review of Bunium persicum: A Valuable Medicinal Spice. Issue 2 (17th February 2023) - Bansal, Sangita; Sharma, Kanika; Gautam, Vikrant; Lone, Ajaz Ahmad; Malhotra, Era Vaidya; Kumar, Sandeep; Singh, Rakesh
ABSTRACT: Bunium persicum (Boiss), B. Fedtsch or Black cumin, is an economically important medicinal spice that is commonly used as a flavour enhancer and preservative in different food systems. It has also been used in Unani, Iranian, and Indian systems of traditional medicine. A member of the Apiaceae family, it possesses myriad phytochemicals, mainly cuminaldehyde, α-terpinene-7-al, γ-terpinene-7-al, γ-terpinene, ρ-cymene, β-Pinene, etc. and endows various proven therapeutic properties including antioxidant, antimicrobial, anti-inflammatory, lipid/glucose lowering activity, anti-carcinogenic activities, etc. This plant grows in the wild in specific areas and is scarcely available and over-exploited; hence, its conservation (both, in vitro and in situ ) is a major concern. Besides, negligible work has been done for molecular characterisation, identification and development of promising high yielding cultivars/varieties of this valuable plant. With the aim to attract the attention of potential stakeholders towards the immense potential and infinite qualities of black cumin, this review provides an insight in to the phytochemistry, economic importance, including food and therapeutic uses; morphological, biochemical, and molecular characteristics of Bunium persicum, along with the efforts towards its conservation and a way forward. Abbreviations BPEO: Bunium persicum essential oil; BPE: B. persicum extract; MPEO: Mentha piperita essential oil; DPPH: 2, 2-Diphenyl-1-picrylhydrazyl; TBA: Thiobarbituric acid; TPC: Total phenolic content; LD50 : Lethal dose; IC50 : Half maximal inhibitory concentration; BHT: Butylated hydroxy toluene; BHA: Butylated hydroxy anisole; ABTS: 2, 2ʹ-Azino-bis (3-ethyl benzo thiazoline-6-sulphonic acid); MICs: Minimum inhibitory concentrations; BSA: Bovine serum albumin; MS: Murashige and Skoog Medium; MSN: Murashige and Skoog medium with Nitsch Vitamins; B5 : Gamborg's Medium; 2, 4-D: 2, 4-dichlorophenoxyacetic acid; Kin: Kinetin; JA: Jasmonic acid; IAA: Indole-3-acetic acid; BAP: 6- Benzylaminopurine; IBA: Indole-3-Butyric Acid; TDZ: Thidiazuron; GA3 : Gibberellic Acid; ABA: Abscisic Acid.